Ultrastructural studies of bovine and swine Sarcocystis species - Dela Pena, Cesar S. (Animo Repository, 2001)
This paper documents the first report of S. cruzi and S. miecheriana in Philippine homegrown cattle and native swine, respectively. Rounded, globular to oval, and spindle-shaped sarcocysts were found in unstained cervicalm pharyngeal, diaphragm, and cardiac muscle tissue smears of 9 out of the 580 homegrown cattle muscle samples examined. Mature fusiform or spindle-shaped sarcocysts measure 183-417 um long and 20-98um wide. Sarcocysts have numerous bradyzoites and some metrocytes within well defined compartments. The sarcocyst wall or parasitophorous vacuolar membrane (PVM) consists of minute hair-like closely packed villar protrusions (VP) of varied length (1.7-2.9um) and width (0.08-0.40um). Ground substance is 0.25-0.70um thick. Middle and distal segments of VP are bent approximately 45-90 degrees and run parallel to the cyst wall surface. Distal ends of the VP at some points join collectively to form conical tufts. The base of the PVM contains numerous minute (0.07-0.0um) bubble-like undulations. Sarcocystis cruzi (Hasselmann, 1926) Wenyon, 1926 cyst wall ultrastructure typifies Type 7 sarcocyst wall, and exhibit striking ultrastructural similarities with the redescribed bubaline S. levinei (Dissanaike and Kan, 1978) Huong, Dubey and Uggla, 1997 in Vietnam and in the Philippines. Sarcocysts of S. miescheriana (Kuhn, 1965) Labbe, 1899 were found in 9 unstained tissue smears of the cervical, pharyngeal and diaphragm, but not in the heart muscle of 205 native swine muscle samples examined. Mature oval sarcocysts measure 22-103um by 31.4-138.2um, and have compartmentalized arrangement of bradyzoites and metrocytes. Sarcocysts wall, or the PVM, consists of tightly packed and tongue-shaped/pallisade-like VP. Cyst wall bears no VP surface undulations, and exhibit electron dense wall about 0.25um thick. Depending on the angle of tissue sections, VP measure 4.2-6um tall and 0.6-1.63um wide. Ground substance 0.7-1.1um thick. Invaginations are present at the primary cyst wall, spaced 0.40-0.92um deep between VP. Ultrastructural description of S. miescheriana cyst wall typifies the Type 10 cyst wall. Pathological findings include displacement/damage to muscle cells including the myofirils and myofilaments, and necrosis of the mitochondria.